Differences in Resource Utilization Between Patients With Diabetes Receiving Glycemia‐Targeted Specialized Nutrition vs Standard Nutrition Formulas in U.S. Hospitals. (16th September 2014) - Hamdy, Osama; Ernst, Frank R.; Baumer, Dorothy; Mustad, Vikkie; Partridge, Jamie; Hegazi, Refaat
Abstract : Objectives: The purpose of the study was to compare patient outcomes and costs for patients with diabetes mellitus (DM) receiving glycemia‐targeted specialized nutrition (GTSN) with similar patients receiving standard nutrition (STDN) formulas during acute care hospitalizations. Research Design and Methods : The study was designed as a retrospective analysis over a 10‐year period (2000–2009) of clinical and cost data from 125, 000 hospital inpatient episodes in the Premier Research Database. Patients received either GTSN or STDN, by tube or orally, as a component of comprehensive care for hyperglycemia in patients with DM. To adjust for potential cohort imbalances, GTSN patients were matched with STDN patients on the basis of propensity scores, adjusting for many characteristics, including age, sex, race, All Patient Refined Diagnosis‐Related Group (APR‐DRG) illness severity, APR‐DRG mortality risk, and comorbidities. Results : Tube‐fed patients with DM who were provided GTSN had a 0.88‐day (95% confidence interval [CI], 0.73–1.02) shorter length of hospital stay (LOS) on average compared with those patients provided STDN. Orally fed patients with DM who were provided GTSN had a 0.17‐day (95% CI, 0.14–0.21) shorter LOS than did those patients provided STDN. The shorter LOS associated with GTSN contributed to a cost savings of $2586 for tube‐fed patients and $1356 for orally fed patients. Conclusions : The use of GTSN feeding formulas for patients with DM in acute care hospital settings was associated with reduced LOS and inpatient hospital episode cost in comparison to STDN.